2016
DOI: 10.1021/acs.jpcc.6b01351
|View full text |Cite
|
Sign up to set email alerts
|

Exploring an Emissive Charge Transfer Process in Zero-Twist Donor–Acceptor Molecular Design as a Dual-State Emitter

Abstract: The present work reports a new concept on how to diminish dark twist intramolecular charge transfer (TICT) states with the zero-twist D−A systems in order to design frameworks with dual solution and solid-state emission property. The study began with theoretical calculations to understand the structural needs followed by the chemical synthesis of conceptually new two molecular designs, 1 and 2, with zero-twist angle between electron donor and acceptor units linked through a covalent bond and finally their appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 71 publications
0
33
0
Order By: Relevance
“…[5][6][7][8][9] Dual-state emissionc an also be attained by incorporating bulk substituents into molecular structurest op rohibit p-p stacking in the solid state. [10] A zero-twist donor-acceptor molecule was also found as ad ualstate emitter, [11] and ar ecent study showed that D-p-A structures can be used to achieve DSE properties. [12] However,t here is no valid design strategy for designing DSEgens with solvatochromism because of the lack of an investigation into the relationship between structure and DSE property.…”
mentioning
confidence: 99%
“…[5][6][7][8][9] Dual-state emissionc an also be attained by incorporating bulk substituents into molecular structurest op rohibit p-p stacking in the solid state. [10] A zero-twist donor-acceptor molecule was also found as ad ualstate emitter, [11] and ar ecent study showed that D-p-A structures can be used to achieve DSE properties. [12] However,t here is no valid design strategy for designing DSEgens with solvatochromism because of the lack of an investigation into the relationship between structure and DSE property.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17] In general, optical materials take important roles in optoelectronics, as part of transistors, OLEDs, solar cells, lightening agents and light modulators. 18,19 These usual D-p-A molecular architectures play an important role in their photophysics because they not only show high uorescent quantum yields owing to the effective radiative decay of their excited intramolecular chargetransfer (ICT) state but also possess impressive bipolar chargetransporting properties for their constitutive hole-and electrontransporting moieties, [20][21][22][23][24][25] that can be modulated through tuning the groups electron donor and/or acceptor strengths. [26][27][28][29][30] Concerning those functional groups, the organosuldes allow a tuneable electronic behavior that can be easily modulated through a single step oxidation to the respective sulfoxides or sulfones, which are effective electron acceptor groups.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of DSE luminophores is difficult due to the distinct molecular design parameters. To date, reports on the molecular design of DSE luminophores have incorporated the following elements: (i) π-conjugation with a zero-twist donor-acceptor moiety to facilitate emission in solution state [20], (ii) twisted molecular structure to avoid fluorescence quenching in the solid state induced by π/π stacking, and (iii) a V-shaped configuration to enhance intramolecular charge transfer (ICT) and potentially suppress short-range π/π intermolecular interactions [21].…”
Section: Introductionmentioning
confidence: 99%